Response of shallow soil temperature to climate change on the Qinghai–Tibetan Plateau - Xiqiang Wang; Rensheng Chen; Chuntan Han; Yong Yang; Junfeng Liu; Zhangwen Liu; Shuhai Guo; Yaoxuan Song (International Journal of Climatology, 2021)
Under climate change, soil temperature change remarkably influences regional landscapes, ecosystems, hydrological processes, and other parameters. Based on daily soil temperature data from 56 stations from 1965 to 2014, the spatiotemporal variations in shallow soil temperature (0, 5, 10, 15, and 20 cm) on the Qinghai–Tibetan Plateau (QTP) were investigated. The mean shallow soil temperature decreased obviously with altitude both annually and seasonally, except in winter. Primarily dependent on station latitude, the spatial distribution of winter soil temperature was significantly affected by the snow cover conditions. As the soil depth increased, the soil temperature showed a cooling trend in spring and summer but a warming trend in autumn and winter. In the past 50 years, the shallow soil temperature increased considerably on the QTP both annually and seasonally. The warming rate of soil temperature was greatly dependent on station altitude in winter and dependent on latitude in summer and longitude in autumn. Unlike the increasing air temperature that was contributed mainly by winter, the warming rate of soil temperature in winter at depths of 5, 10, 15, and 20 cm was obviously lower than that in other seasons and air temperature in winter. This occurrence may be caused by relatively less snow cover in winter, which produces a weak insulation effect and further makes the soils more vulnerable to cooling from cold air. For the entire region, the soil temperature variability was strongly correlated with the change in air temperature but weakly correlated with precipitation. Although the warming rate in shallow soil tended to be low (high) at stations with a high amount of precipitation (snow cover), the influence of precipitation (including snow) on shallow soil temperature was limited on the QTP in the past few decades.